Reattachment of Fractured Anterior Tooth: A 2-Year Review of a Case (2011)
Injury to anterior teeth is a relatively common occurrence. Dentists are confronted on regular basis with dental trauma and the management. Some clinical studies have reported reattachment of fractured tooth segment using adhesive resin cement and dentine bonding agent with or without intraradicular postplacement. Reattachment of tooth fragment is simple and can provide good functional and esthetic success. Case description: This article reports the reattachment of a fractured anterior tooth in a 17-year-old male patient with adhesive resin and a prefabricated metallic post. Result: Evaluation at 2 years revealed good reattachment, intact post, good esthetics (even after a repeat reattachment) and good periodontal health.